(untitled) (Journal of Environmental Microbiology and Toxicology, 2024)
Lohan River, a small stream near the former Mamut Copper Mine, receives sediment contributions from mine overburden and ultrabasic soils rich in Co, Cr, and Ni. This study investigated heavy metal enrichment in the riverbed sediments. Seven sampling stations were selected along the river, with additional control stations at Lohan Toki River and Moroli River. Heavy metals were extracted using the aqua regia method and analyzed via ICP-OES, with quality control including blanks and SRM digestions. Cr (218–700.68 mg/kg), Ni (238.47–679.22 mg/kg), and Cu (235.19–438.97 mg/kg) concentrations in Lohan River sediments exceeded high guideline values (H-GV) from the Australian and New Zealand Sediment Quality Guidelines (370 mg/kg for Cr, 52 mg/kg for Ni, and 270 mg/kg for Cu). Lohan Toki River sediments also showed Cr and Ni contamination, while Moroli River sediments remained below H-GV. Water samples recorded metal levels below Malaysia’s Class IIA/IIB thresholds. Environmental indices classified Lohan River sediments as moderately to heavily polluted with Cr, Cu, and Ni (Igeo Class 3). Enrichment Factor (EF) values ranged from 4.94 to 11.67, indicating significant enrichment. Pollution Load Index (PLI) values showed localized moderate to heavy pollution at Stations 5 and 6. However, the values of Potential Ecological Risk Index (PERI) were below 150, indicating low ecological risk overall. Despite localized contamination, the water’s heavy metal levels posed no immediate threat under current standards.